Cuidados paliativos realizados por profesionales de enfermería en adultos con Esclerosis Lateral Amiotrófica (ELA) - Borda Salazar, Laura Fernanda (Universidad Antonio Nariño, 2023)
To describe the palliative care provided by nursing professionals in adults with amyotrophic lateral sclerosis (ALS). Methodology: In this study, a narrative review of the literature was used, which was based on the five phases proposed by Whittemore and Knafl. During the evaluation and analysis phase of the data collected in the review, it was decided to create a matrix in Excel in order to facilitate the organization and processing of information.